Principles of IP-Court Activity in Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The principles of IP-court activity in Ukraine have been studied. It has been emphasized that the urgent issues currently are to review the existing approaches to reforming the judicial system of Ukraine, based on the gained experience of establishing specialized courts, defining principles as guidelines for the functioning of IP-court in Ukraine as the Higher Specialized Judicial System of Ukraine.The concept of “principles” and their classification have been defined. The author has noted the importance of international principles of court activity in Ukraine. The regulatory base of courts activity has been characterized, where the principles of functioning of courts and judges in Ukraine have been defined. The author has singled out such an international legal document as the Basic Principles of Judicial Agencies’ Independence, which enshrines the following principles of IP-court activity in Ukraine: the principle of judicial agencies’ independence; the principle of freedom of speech and associations; the principle of qualification, selection and training; the principle of professional secrecy and immunity.The category of “principles of IP-court activity in Ukraine” has been offered to understand as a set of guiding (fundamental) ideas, grounds, principles of operation and functioning of IP-court in Ukraine that ensure the proper administration of justice, respect for rights and fundamental freedoms during the trial and ensuring the right to a fair trial.The principles of the IP-court activity in Ukraine are as follows: 1) general and legal: the rule of law principle; the principle of observance of human rights and fundamental human and civil freedoms; the principle of legality; the principle of openness and transparency of court proceedings; the principle of political or other impartiality; the principle of reasonable terms; 2) special principles of IP-court activity in Ukraine: the principle of independence of judicial agencies; the principle of freedom of speech and associations; principle of qualification; the principle of professional secrecy.It has been concluded that enshrining the principles of operation and functioning of the Supreme Court on Intellectual Property Issues in the Law of Ukraine “On the Supreme Court on Intellectual Property Issues” will increase the efficiency of the judicial system of Ukraine and significantly affect the authority and prestige of IP-court in Ukraine.